Coordination and space confined preparation of nickel sub-nanoparticles within a metal-organic framework for catalytic degradation of methyl orange. Issue 5 (October 2020) - Li, Zhouxun; Zhang, Hui; Kong, Lingtao; Chen, Zhenxia; Yang, Yongtai; Liu, Xiaofeng; Deng, Mingli; Zhou, Yaming
Graphical abstract: Nickel sub-nanoparticles were prepared by coordination-space confinement strategy within a metal-organic framework. Highlights: Highly dispersed Ni sub-nanoparticles with the size around 1∼2 nm were derived from the MOF of UiO-67-NN. The UiO-67-NN support has a coordination-confinement effect on the Ni(NO3 )2 precursor. The resulting nickel sub-nanoparticles are space-confined within the UiO-67-NN structure. Ni@UiO-67-NN-P composite serves as an efficient catalyst for the degradation of methyl orange dye. Abstract: Nickel nanoparticles are a kind of promising heterogeneous catalysts. However, highly dispersed Ni sub-nano particles (SNPs) encapsulated in carbon composites are rarely reported due to their tendency to aggregate and the lack of strong interactions between Ni 2+ precursors and carbon materials. In this work, we present a facile coordination-space confinement strategy to prepare Ni SNPs@carbon composites by using a metal organic framework of UiO-67-NN as support. Utilizing the coordination interaction between Ni 2+ ions and 2, 2′-bipyridine-5, 5′-dicarboxylate (NN-bpdc) ligands from the supports, the impregnated Ni 2+ ions were stoichiometrically fixed and then in-situ transferred into NiO SNPs in the first pyrolysis process. Owing the space-confinement of UiO-67-NN, these NiO SNPs were then in-situ reduced into Ni SNPs with the size around 1∼2 nm, which were uniformly dispersed in the carbon composite derived from UiO-67-NN. Detailed studies revealed that the coordination-space confinement also played a vital role in the in-situ pyrolysis process of Ni 2+ → NiO → Ni 0 . The degradation percentage of methyl orange dye in the presence of Ni@UiO-67-NN-P composite was higher than those reference catalysts prepared in conditions without either coordination or space confinement. The present work provides a potential strategy for the preparation of metallic SNPs catalysts with high efficiency.